2020
DOI: 10.30630/joiv.4.1.280
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The Strategy Detection on Information Security in Corporate Organizations on Crucial Asset

Abstract: Information Security is a crucial asset within an organization, and it needs to be protected, Information System (IS) Security is still threats a significant concern for many organizations. Is profoundly crucial for any organization to preserve Information System (IS) Security and computer resources, hardware, software, and networks, etc.The Information System (IS)assets against malicious attacks such as unauthorized access and improper use. This research, we developed a theoretical model for the adoption proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Nevertheless, some parallels between approaches exist. Some universal cybersecurity goals include acquiring cyber resilience, protecting vital information infrastructures, reducing cybercrime, and contributing to building global cyberspace guidelines (Makeri, 2020). Kumar et al (2020) suggested five necessary considerations for developing effective cybersecurity strategies: clear vision, security governance, security risk management, reward strategies for workers, and information sharing about cybersecurity threats and criminals.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some parallels between approaches exist. Some universal cybersecurity goals include acquiring cyber resilience, protecting vital information infrastructures, reducing cybercrime, and contributing to building global cyberspace guidelines (Makeri, 2020). Kumar et al (2020) suggested five necessary considerations for developing effective cybersecurity strategies: clear vision, security governance, security risk management, reward strategies for workers, and information sharing about cybersecurity threats and criminals.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Organizations must prepare a variety of corresponding safeguard strategies and countermeasures to ensure adherence to cybersecurity guidelines and regulations through consistently evaluating possible or real cybersecurity violations (Longley, 2019). Many previous studies have demonstrated that normative pressure is an important driver for enhanced information security compliance (Makeri, 2020). Jeyara and Zadeh (2020) argued that organizations are increasingly pressured to respond to cyber threats as cybersecurity awareness and solutions have developed, impacting the professionals they employ, the solutions they adopt, and the strategies with which they manage professional circumstances.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…The system in [2] provides two methods to implement home security using IOT. One of using web cameras such that whenever there is any motion detected by the camera, it sounds an alarm and sends a mail to the owner [22,23,24]. This method of detecting intrusion is quite good but somehow expensive due to the cost of cameras involved in the process [3, 25, 26,].…”
Section: Introductionmentioning
confidence: 99%
“…If there is an object movement in the room, the intensity changes and detecting the object movement takes place. The PIR Sensor is small in size, inexpensive in price, uses low power, easy in use and connectivity[21][22]…”
mentioning
confidence: 99%